Finance of International Trade in the Gulf - Al-Suwaidi, Ahmed A. M. S., (Arab and Islamic Laws Series ;, 1994)
This book analyses the legal structure and operation of the conventional and Islamic banking systems in the Gulf Arab states. It defines the legal issues involved and case law decided by the English, American and the Gulf Arab states courts in operating the two systems in financing the international trade transactions and covering the concurrent application, the advantages and disadvantages and the problems of each system. This book also gives a particular challenge to the fraud in international trade and considers the development of countertrade and electronic funds transfer as methods of financing some of the international business transactions. This book is very helpful for those who are dealing with the financing of the international trade, their professional advisors, staff of the conventional and Islamic banks and students who study law and commerce as part of their syllabuses of legal and international business studies. This book is also very essential reading for anyone who wants to succeed in the competitive conditions of modern banking business vis-a-vis the international trade in the Gulf Arab states. This book is also very helpful for the lawyer who is called upon to assist the businessman in his ventures or who wants to resolve a problem which has arisen in financing the international business transactions.